Genistein Prevents Cadmium-induced Neurotoxic Effects through its Antioxidant Mechanisms - Gong, D.-k.; Liu, B.-h.; Tan, X.-h. (Drug Research, 2015)
Introduction: Cadmium-induced neurotoxic effects are mediated through adverse oxidative stress and calcium signaling. Genistein, a phytoestrogen is a potent antioxidant and exhibits property to cross blood-brain barrier.Methods: Experimental model of cadmium-induced neurotoxic effects were induced by treatment with cadmium (5 mg/kg) for 28 days in wistar rats. For determining the protective effect, genistein was administered at a dose of (10 mg/kg) for 7 days followed by cadmium treatment for 28 days. Serum and tissues were analyzed for various oxidative stress markers such as total antioxidant capacity, total oxidant levels, non-enzymic antioxidants, enzymic antioxidants, lipid peroxide levels and protein carbonyl content.Results: The results showed significant increase in the oxidative stress markers during cadmium treatment was attenuated in rats treated with genistein followed by cadmium treatment. In addition, cadmium induced alterations and activities of ATPase were significantly restored by genistein treatment.Conclusion: The present study observations show promising results of genistein against cadmium-induced neurotoxic effects in wistar rats. Thus its potent antioxidant and cytoprotective effects could act as potent therapeutic agent against various neuro-degenerative diseases involving oxidative stress as primary mechanism.
Keywords: neuroprotection; ATPases; oxidative stress; genistein; cadmium